2019
DOI: 10.1071/py19007
|View full text |Cite
|
Sign up to set email alerts
|

Association of health literacy and diabetes self-management: a systematic review

Abstract: The purpose of this review is to summarise the existing evidence about the association of health literacy (HL) with type 2 diabetes mellitus self-management. The PubMed, Medline, CINHAL, Scopus and Web of Science databases were searched for randomised control trials of type 2 diabetes mellitus (T2DM) self-management and HL published between 2009 and 2018. Fourteen randomised control trials were included in this review. Our findings showed that HL was instrumental in improving diabetes knowledge, physical activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 31 publications
(107 reference statements)
3
61
1
1
Order By: Relevance
“…In this regard, controversial findings have been reported in various studies. For example, in a study by Couture et al (2017) [42] no association was found between HL and the QOL, while one systematic review study demonstrated that higher HL leads to significant improvement in T2DM-related QOL [43]. A meta-analysis on this relationship would be helpful for further research.…”
Section: Discussionmentioning
confidence: 98%
“…In this regard, controversial findings have been reported in various studies. For example, in a study by Couture et al (2017) [42] no association was found between HL and the QOL, while one systematic review study demonstrated that higher HL leads to significant improvement in T2DM-related QOL [43]. A meta-analysis on this relationship would be helpful for further research.…”
Section: Discussionmentioning
confidence: 98%
“…(2017) [45] no association was found between HL and the HRQL, while one systematic review study demonstrated that higher HL leads to signi cant improvement in T2DM-related HRQL [46]. A metaanalysis on this relationship would be helpful for further research.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, controversial findings have been reported in various studies. For example, in a study by Couture et al [ 45 ] no association was found between HL and the HRQL, while one systematic review study demonstrated that higher HL leads to significant improvement in T2DM-related HRQL [ 46 ]. A meta-analysis on this relationship would be helpful for further research.…”
Section: Discussionmentioning
confidence: 99%